(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
The use of metallic materials is very important for our society, and corrosion is a spontaneous degradation process that turns their application harder and more expensive. Therefore, alternative and cheap methods for the reduction or elimination of this process are necessary, as drugs with anti-corrosive properties. The objective of this study was measuring the efficiency, through gravimetric analysis in acid media (HCl 1M), of Dipyrone Monohydrate and Ticlopidine Hydrochloride as corrosion inhibitors, on four materials: steel, cast iron, brass and aluminum. The Ticlopidine Hydrochloride on steel had the max efficiency of 99,17% and the Dipyrone Monohydrate on brass had the minimum efficiency of 0,22%.